Diseño de una aplicación móvil turística para la identificación de geositios – Geoparque Imbabura - Rocha Estévez, Alexander Ismael (2023)
This thesis focuses on the design of a tourist mobile application to improve the experience of visitors in the Imbabura Geopark, Ecuador. The main purpose is to provide a reference and information tool that facilitates the exploration and identification of geosites in this region rich in geological and cultural heritage. The Imbabura Geopark is home to a wide variety of geosites, ranging from unique geological formations to breathtaking landscapes and significant cultural sites. Despite this potential, the lack of easily accessible information may limit appreciation and tourism in the geopark area. The approach of this thesis is multidisciplinary, fusing technological, geological and tourist aspects. The methodology begins with a meticulous study of the geosites in collaboration with experts in geology and cultural heritage. This stage is crucial to ensure that the information provided in the application is accurate, complete and up-to-date. The design of the application focuses on the user experience. A friendly and easy-to-navigate interface is created, allowing users to quickly and intuitively access details about each geosite. The application includes georeferenced maps, photographs and detailed descriptions, providing a comprehensive overview of the importance and characteristics of each place. To ensure the effectiveness of the application, pilot tests are carried out with a representative group of users, both tourists and local residents. The feedback obtained is used to optimize the app before its official release. Once the application is complete, a promotion strategy is implemented in collaboration with local authorities and tourism agencies. Awareness campaigns are carried out and tourist events are used to publicize the usefulness of the application, encouraging visitors to download it and use it during their stay at the Imbabura Geopark.